Progression of Contralateral Hearing Loss in Patients With Sporadic Vestibular Schwannoma - Early, Samuel; Rinnooy Kan, Charlotte E.; Eggink, Maura; Frijns, Johan H. M.; Stankovic, Konstantina M. (Frontiers in Neurology, 2020)
Background and Introduction: Vestibular schwannomas (VSs) are the most common tumors of the cerebellopontine angle, typically presenting unilaterally with ipsilateral sensorineural hearing loss (SNHL). The mechanism of tumor-induced hearing loss has recently been shown to be related to secreted tumor factors, in addition to mechanical compression of the adjacent auditory nerve, and these factors may percolate through CSF or blood to affect contralateral hearing as well. Methods: This is a retrospective study of medical records for patients treated for VS at Mass Eye and Ear from January 1994 through October 2018. Included patients had unilateral VS and sequential audiometry allowing for longitudinal assessment of hearing over time. Mass Eye and Ear's audiology database was used to select age- and sex-matched case controls, also with sequential audiometry, from the non-VS population. Subgroup analysis was performed by age, sex, baseline hearing, and tumor size at initial diagnosis. Hearing loss progression was performed using Kaplan-Meier analysis to account for variable follow-up times. Results: A total of 661 patients were identified with VS and sequential audiometry. The population was predominantly female vs. male (368 vs. 293, p = 0.0035), driven primarily by younger patients with Koos 4 tumors (76 female vs. 49 male, p = 0.016). Patients with normal baseline hearing bilaterally (N = 241) demonstrated no significant difference in hearing loss progression in VS-contralateral vs. control ears. Patients with abnormal baseline VS-ipsilateral hearing (N = 190), however, demonstrated significantly higher likelihood of reaching moderate SNHL in VS-contralateral ears. Subgroup analysis by age, sex, and baseline tumor size did not yield any subgroup-specific trends for hearing loss progression. Discussion and Conclusion: This is the largest study to date tracking long-term bilateral hearing outcomes in patients with VS, and demonstrates that, in patients with abnormal hearing in the VS-ipsilateral ear, there exists a long-term risk of progression to moderate hearing loss in the contralateral ear as well. Combined with the absence of significant changes in word understanding in the affected ears, these findings may provide clues to the nature of tumor-secreted factors involved in VS-associated hearing loss. Female predominance within the VS patient population is confirmed, driven mostly by younger female patients with Koos 4 tumors.